The Household's Attitude Impacts The Low Use of Latrines in RW 02 Gempolklutuk, Tarik, Sidoarjo - Renita Diah Paramita; Lilis Sulistyorini (Universitas Airlangga, 2016)
Abstract: Gempolklutuk is village with the lowest of access latrines achievement in Tarik, Sidoarjo. The low of access latrines achievements show that there are people who still defecate in the river.This research was to analyze the influence factors toward the low use of latrines in RW 02 Gempolklutuk, Tarik, Sidoarjo. This research was analytic with cross sectional design. The samples was taken from population by simple random sampling. Interviews was held to 57 household's in RW 02, Desa Gempolklutuk. The instrument used questionnaire. The collected data was sorted and analyzed. The analysis showed that household's attitude have infl uence toward the low use of latrines (p-value = 0.000). Good household's attitude will be followed by good use of latrines. The moderate household's attitude become barrier of using latrine. Education and income level, knowledge, house distance to river, family and community support factors had no effect in using latrine. It is concluded that household's attitude was the most infl uence factor toward the low use of latrines. It is suggested to health worker or Sidoarjo's Health Department to giving guidance for household's who didn't have latrines to increase using latrine.Keywords: attitude, household, latrine